Petroleum contaminated water and health symptoms: a cross-sectional pilot study in a rural Nigerian community. Issue 1 (December 2015) - Kponee, Kalé; Chiger, Andrea; Kakulu, Iyenemi; Vorhees, Donna; Heiger-Bernays, Wendy
Abstract Background The oil-rich Niger Delta suffers from extensive petroleum contamination. A pilot study was conducted in the region of Ogoniland where one community, Ogale, has drinking water wells highly contaminated with a refined oil product. In a 2011 study, the United Nations Environment Programme (UNEP) sampled Ogale drinking water wells and detected numerous petroleum hydrocarbons, including benzene at concentrations as much as 1800 times higher than the USEPA drinking water standard. UNEP recommended immediate provision of clean drinking water, medical surveillance, and a prospective cohort study. Although the Nigerian government has provided emergency drinking water, other UNEP recommendations have not been implemented. We aimed to (i) follow up on UNEP recommendations by investigating health symptoms associated with exposure to contaminated water; and (ii) assess the adequacy and utilization of the government-supplied emergency drinking water. Methods We recruited 200 participants from Ogale and a reference community, Eteo, and administered questionnaires to investigate water use, perceived water safety, and self-reported health symptoms. Results Our multivariate regression analyses show statistically significant associations between exposure to Ogale drinking water and self-reported health symptoms consistent with petroleum exposure. Participants in Ogale more frequently reported health symptoms related to neurological effects (OR = 2.8), hematological effects (OR = 3.3), and irritation (OR = 2.7). Conclusions Our results are the first from a community relying on drinking water with such extremely high concentrations of benzene and other hydrocarbons. The ongoing exposure and these pilot study results highlight the need for more refined investigation as recommended by UNEP.